Phase motion transducer - R. A. Akhmedzhanov; V. F. Chegodaev; A. I. Cheredov; A. V. Shchelkanov (Омский научный вестник)
The principle of construction of a multipole phase transducer with a running field with the implementation of multiphase winding located in one plane is considered. This transducer has high operational reliability and can be mounted on curved surfaces.